Antiplasmodial Activity and Toxicological Study of Two Anti-Malarial Herbal Medicines, Balm of Gilead (BOG) and Prolife Herbal Medicine (Prolife) in Infected Albino Mice - Orji, Esther Anya; Eze, Chinwe Nwadiuto (British Journal of Healthcare and Medical Research, 2023)
The treatment of malaria is becoming more challenging due to the problem of resistance and poverty. The present study investigated the antimalarial activity and toxicity of two herbal medicines: Balm of Gilead and Prolife antimalarial drugs. Malaria infection was established by inoculating mice with 1 ×107 parasitized blood (Plasmodium berghei) and treatment was done by a single dose of 100mg/kg herbal medicines given once a day in a curative (Rane's test) and prophylactic tests. The results were compared with standardized medicines; Chloroquine/Fansider and Lonart. Histology of liver, kidney and spleen was conducted after the treatment period. On Day14 post treatment, BOG and Prolife had average parasitemia level of 3.63 ±0.80 and 3.88 ±0.87 and average parasite suppression of 73.5% and 63.4% respectively. In the prophylactic treatment, BOG and Prolife had average parasitemia level 7.01 ± 0.07 and 10.92 ± 0.02 respectively. The negative control showed increased level of parasitemia at Day 14. The results showed that BOG and PROLIFE exhibited considerable antimalarial potential. On the other hand, the histology results showed mild distortion on the liver and spleen but safe to the kidney. Therefore, in as much as these drugs can cure and prevent malaria, they can also be a potential health threat if not taken properly with caution. I suggest regulatory bodies and pharmaceutical companies should under study the active ingredients for preparations of these anti-malaria drugs.